2019
DOI: 10.1155/2019/3560640
|View full text |Cite|
|
Sign up to set email alerts
|

Nivolumab and Ipilimumab in the Treatment of Metastatic Uveal Melanoma: A Single-Center Experience

Abstract: Background. Metastatic uveal melanoma (MUM) is associated with a poor prognosis, with a median overall survival (OS) of 4–15 months. Despite new insights into the genetic and molecular background of MUM, satisfactory systemic treatment approaches are currently lacking. The study results of innovative treatment strategies are urgently needed. Patients and Methods. This was a retrospective case series of 8 patients with MUM managed at the University of Cincinnati between January 2015 and January 2018. The immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…A high number of patients developed severe ICB-related AEs of grade 3 (24 patients, 37.5%) and grade 4 (1 patient, 1.6%) [130]. Furthermore, Karivedu et al [131] published a retrospective analysis of eight metastatic UM patients who were treated with transarterial chemoembolization (TACE) and a combined ICB with nivolumab and ipilimumab. The median OS was 14 months and the median PFS was not reported.…”
Section: Combination Therapies/combined Icb: Ctla-4 and Pd-1 Blockadementioning
confidence: 99%
See 1 more Smart Citation
“…A high number of patients developed severe ICB-related AEs of grade 3 (24 patients, 37.5%) and grade 4 (1 patient, 1.6%) [130]. Furthermore, Karivedu et al [131] published a retrospective analysis of eight metastatic UM patients who were treated with transarterial chemoembolization (TACE) and a combined ICB with nivolumab and ipilimumab. The median OS was 14 months and the median PFS was not reported.…”
Section: Combination Therapies/combined Icb: Ctla-4 and Pd-1 Blockadementioning
confidence: 99%
“…Four patients developed treatment-related colitis; however, the severity of the AEs was not clearly reported. [131]. In a retrospective population-based study, Bol et al [115] evaluated the efficacy of a combined therapy with ipilimumab and nivolumab in 19 patients.…”
Section: Combination Therapies/combined Icb: Ctla-4 and Pd-1 Blockadementioning
confidence: 99%
“… 219 221 Analysis of eight cases enrolled in a single-center trial indicated that metastatic UM patients treated with the combination of nivolumab and ipilimumab through transarterial chemoembolization (TACE) had a 25% PR rate and 50% SD rate. 222 A largescale phase II trial, GEM1402, was conducted with the combination of ipilimumab + nivolumab in a group of 50 metastatic UM patients. The ORR and SD rates were 12% and 52%, respectively [ClinicalTrials.gov identifier: NCT02626962].…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…In cutaneous melanoma, combined checkpoint blockade with ipilimumab and nivolumab revealed response rates and survival outcomes superior to PD-1 inhibitor monotherapy, albeit at the cost of high immune-related toxicity [10]. However, the significance of combined checkpoint blockade in UM is unclear and has only been investigated in case reports and small case series [6,11,12]. In this study, we evaluate the clinical course of 64 patients with metastatic UM who received combined checkpoint blockade.…”
Section: Introductionmentioning
confidence: 99%